Program Potensi Desa dan Desa Tanggap Bencana Desa Giring Kecamatan Paliyan Gunungkidul - Putra, Libertus Anggit Martini L; Pima, Nike Naka; Zwageri, Lorenzo Baptista; Wicaksana, Dhaniel Satria; Kinesto, Pius Bagas Vando; Krisnawardhani, Katarina Intan Rizky; Setiawan, Agnes Nathalia Pramudyanti; Juniyati, Juniyati; Mulyadi, Fani; Prianda, Elga Ariana; Widiastiani, Nindry Sulistya (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2021)
Desa Giring is one of the many villages in Paliyan District, Gunungkidul which has a lot of potentials that can be developed further. The village potential includes traditional culture, agricultural and livestock products, as well as tourist objects. In its development efforts, it is necessary to introduce this potential to the wider community in order to attract tourists, thereby increasing the activities of the tourism sector. In addition, considering the potential for natural disasters that may occur in Desa Giring, an educational effort to the public about natural disaster prevention and precaution measures are deemed necessary by making pocketbooks as a medium of information. Data collection in the form of Desa Giring profiles, village potentials, and ways of dealing with natural disasters was carried out by means of literature studies through journals, articles, and the internet. The results of the literature study in the form of information findings and theoretical studies are then compiled in the form of videos and e-books. The output of the first work program, namely the e-book and video of Potensi Desa Giring which discusses the potentials in the village, while the output of the second work program, namely e-books and videos of the Buku Saku Desa Tanggap dan Sigap Bencana, which discusses prevention and precaution measures of natural disasters that have the potential to occur in Desa Giring. Hopefully, the two outputs of the programs can be used in future village development activities and give insight into how to do natural disaster prevention and precaution.